Unprecedented distribution data for Joshua trees (Yucca brevifolia and Y. jaegeriana) reveal contemporary climate associations of a Mojave Desert icon - Esque, Todd C.; Shryock, Daniel F.; Berry, Gabrielle A.; Chen, Felicia C.; DeFalco, Lesley A.; Lewicki, Sabrina M.; Cunningham, Brent L.; Gaylord, Eddie J.; Poage, Caitlan S.; Gantz, Gretchen E.; Van Gaalen, Ross A.; Gottsacker, Ben O.; et al. (Frontiers in Ecology and Evolution, 2023)
Forecasting range shifts in response to climate change requires accurate species distribution models (SDMs), particularly at the margins of species' ranges. However, most studies producing SDMs rely on sparse species occurrence datasets from herbarium records and public databases, along with random pseudoabsences. While environmental covariates used to fit SDMS are increasingly precise due to satellite data, the availability of species occurrence records is still a large source of bias in model predictions. We developed distribution models for hybridizing sister species of western and eastern Joshua trees (Yucca brevifolia and Y. jaegeriana; respectively), iconic Mojave Desert species that are threatened by climate change. We conducted an intensive visual grid search of online satellite imagery for 672,043 0.25 km 2 grid cells to identify the two species' presences and absences on the landscape with exceptional resolution, and field validated 29,050 cells in 15,001 km of driving. We used the resulting presence/absence data to train SDMs for each Joshua tree species, revealing the contemporary environmental gradients (during the past 40 years) with greatest influence on the current distribution of adult trees. While the environments occupied by Y. brevifolia and Y. jaegeriana were similar in total aridity, they differed with respect to seasonal precipitation and temperature ranges, suggesting the two species may have differing responses to climate change.Moreover, the species showed differing potential to occupy each other's geographic ranges: modeled potential habitat for Y. jaegeriana extends throughout the range of Y. brevifolia, while potential habitat for Y. brevifolia is not well represented within the range of Y. jaegeriana. By reproducing the current range of the Joshua trees with high fidelity, our dataset can serve as a baseline for future research, monitoring, and management of this species, including an increased understanding of dynamics at the trailing and leading margins of the species' ranges and potential for climate refugia.